Meaning-Making Lenses in Counselling: Discursive, Hermeneutic-Phenomenological, and Autoethnographic Perspectives - Strong, Tom; Pyle, Nathan R.; deVries, Cecile; Johnston, Dawn N.; Foskett, Allison J. (Canadian Journal of Counselling and Psychotherapy, 2008)
Counselling can be seen as a context or process for meaning-making where clients and counsellors actively interpret and construct meaning. We examine meaning-making in counselling through the lenses of three research methods: (a) discourse analysis, (b) hermeneutic-phenomenology, and (c) autoethnography. Specifically, we relate the process and experience of counselling in ways consistent with how meaning-making is regarded by each of these research methods. In this regard, we describe each method as if it was a counselling theory. We conclude by reflecting upon how these lenses on meaning-making and counselling can inform counselling practice generally and generatively.